2015
DOI: 10.2147/tcrm.s81623
|View full text |Cite
|
Sign up to set email alerts
|

Association of diabetes-related distress, depression, medication adherence, and health-related quality of life with glycated hemoglobin, blood pressure, and lipids in adult patients with type 2 diabetes: a cross-sectional study

Abstract: This study examined the associations of diabetes-related distress (DRD), depressive symptoms, health-related quality of life (HRQoL), and medication adherence with glycemia, blood pressure (BP), and lipid biomarkers in adults with type 2 diabetes mellitus (T2D). This cross-sectional study was conducted in three Malaysian public health clinics in 2012–2013, recruited adult patients (aged ≥30 years) with T2D who had been diagnosed for more than one year, were on active follow-up, and had recent blood test result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 55 publications
2
15
0
1
Order By: Relevance
“…In the United States of America and South Africa studies, they found similar DD-related factors, such as younger age and lower levels of public healthcare support [10,11]. Two studies in Malaysia revealed that being female, having higher levels of systolic blood pressure [12], having a level of HbA1c more than 8.5%, the presence of comorbid, lifestyle and family history of psychiatric illness were all highly associated with a high level of DD [13]. Furthermore, an Iran study reported that being female and the level of education to be the significant predictors of DD [14].…”
Section: Introductionmentioning
confidence: 90%
“…In the United States of America and South Africa studies, they found similar DD-related factors, such as younger age and lower levels of public healthcare support [10,11]. Two studies in Malaysia revealed that being female, having higher levels of systolic blood pressure [12], having a level of HbA1c more than 8.5%, the presence of comorbid, lifestyle and family history of psychiatric illness were all highly associated with a high level of DD [13]. Furthermore, an Iran study reported that being female and the level of education to be the significant predictors of DD [14].…”
Section: Introductionmentioning
confidence: 90%
“…Both instruments were also associated with quality of life [13][14][15], but with medication adherence only an association was found with PAID-20 [13; 16]. In terms of disease control, PAID-20 was associated with poor glycemic control (HbA1c > 8%) [14; 17], while higher DDS-17 scores were associated with lower systolic blood pressure (adjusted B= -0.08, P=0.066), and no association was observed with lipid profiles with DDS-17 but yet to be investigated with PAID [17]. To summarize, it is currently unclear whether the choice for a certain measure of DD will lead to different conclusions when used in the same population with regard to its association with patientreported and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It has a negative impact on individuals, affecting all spheres of life and reducing their quality of life [7,8]. The psychosocial [9] and psychological [10,11] problems associated with diabetes, as well as the burden of disease and the lifestyle restrictions of diabetic patients are widely addressed in the literature [12]. For these reasons, individuals with DM need ongoing professional support and specific training to minimize complications and improve their well-being [13][14][15].…”
Section: Introductionmentioning
confidence: 99%